Pengukuran Profitabilitas Perbankan Sebelum dan Sesudah Mengimplementasikan Teknologi Blockchain (Studi Kasus Pada Bank AlHilal) - Sya'bana, Sasmita Wahyu; Noval, Muhammad; Marpaung, Muslim (Jurnal Ilmiah Ekonomi Islam, 2024)
Financial technology emerged as a result of the rapid development of the internet and information technology, which is increasingly sensitizing the public, often known as Financial Technology. Collaboration between FinTech and banking institutions will provide benefits for both parties. The purpose of this study is to evaluate the impact of banking and FinTech cooperation, especially with regard to blockchain technology. This study uses a quantitative approach with comparative analysis to evaluate the variation in profitability levels determined by the Return on Equity (ROE), Return on Assets (ROA), and Net Profit Margin (NIM) ratios between before and after implementing blockchain technology at Al Hilal Bank for the period 2012 to 2023. The paired sample t-test was used to assess the data, and the results showed that there was no significant difference between ROA, ROE, and NPM after using blockchain technology. The implications of this study indicate that banks still need to make improvements and adjustments in order to remain optimally profitable while keeping up with technological developments.